What's up (what is single-use plastics) a coomunication plan to modify the attitude and self efficacy of Barangay Mintal residents to reduce their single-use plastics usage - Ballerta, Frances Alvie F. (2019)
Single-use plastic kill, however because of its numerous functions on the daily lives of the people they tend to neglect its negative effects. Thus A Communication Plan that aims to modify the level of attitude and self-efficacy of the residents from them to develop an intention to reduce their single-use plastics usage was crafted using the Research-Objectives-Programing ?Evaluation or ROPE Process. The research was guided by the self-efficacy theory of Albert Bandura and the theory of planned behavior by Icek Ajzen. Self-efficacy theory states that a person?s behavior is influenced by their confidence to act (Bandura 1977) and TPB states that attitude, subjective norm, and perceive behavioral control affects the intention of the individual to act. Through a mixed method design the survey, Key Informant Interview and Focused Group Discussion. The result of the formative research conducted showed that the self-efficacy attitude, subjective norm, and perceive behavioral control of the residents were correlated to their level of knowledge. Based also on the result the residents have low level of knowledge and they process fallacious knowledge about it. Thus, in order to modify the attitude and self-efficacy of the residents their knowledge must be increased first. The objectives of this communication plan were formulated base on the identified opportunities and problems from the research and crafted in a specific, measurable, attainable, realistic, and time bound (SMART) goals. The programming was based on the research results, the objectives and it was also guided by the Theory of Planned Behavior and Self-Efficacy Theory.